Complication and Sequelae of COVID-19: What Should We Pay Attention to in the Post-Epidemic Era - Yang, Keda; Wen, Guangfu; Wang, Jinpeng; Zhou, Siming; Da, Wacili; Meng, Yan; Xue, Yuchuan; Tao, Lin (Frontiers in Immunology, 2021)
COVID-19 is widespread worldwide and seriously affects the daily life and health of humans. Countries around the world are taking necessary measures to curb the spread. However, COVID-19 patients often have at least one organ complication and sequelae in addition to respiratory symptoms. Controlling the epidemic is only a phased victory, and the complication and sequelae of COVID-19 will need more attention in the post-epidemic era. We collected general information from over 1000 articles published in 2020 after the COVID-19 outbreak and systematically analysed the complication and sequelae associated with eight major systems in COVID-19 patients caused by ACE2 intervention in the RAS regulatory axis. The autoimmune response induced by 2019-nCoV attacks and damages the normal tissues and organs of the body. Our research will help medical workers worldwide address COVID-19 complication and sequelae.